PENGGUNAAN MEDIA BOOKLET UNTUK MENINGKATKAN PENGETAHUAN PERKEMBANGAN MOTORIK KASAR PADA UMUR 6-24 BULAN PADA KADER POSYANDU WILAYAH KERJA UPTD PUSKESMAS SAIGON - Nasiha; Desi; Iman Jaladri (Media Gizi Khatulistiwa, 2024)
Motor development is divided into two, namely gross motor development and fine motor development. Gross motor development involves large muscles, including the development of head, body, limb movements, balance, and movement. The purpose of this study was to determine the increase in knowledge scores before and after the use of booklets to determine the gross motor development of infants aged 6-24 months at the integrated health post in the Saigon Health Center UPTD work area. The type of research conducted was experimental guasi with a one group pre-test - post-test design. The results of the study proved that it could be seen that the average knowledge score before being given counseling was 37.43, but after being given counseling the average increased to 84.86. the difference in knowledge increase before and after being given counseling with booklet media increased by 47.43. The minimum score before counseling was 20 then increased to 60 after being given counseling. The maximum value before counseling was 60 then increased to 100. Based on statistical analysis p value 0.000 <0.05 which means there is a significant difference in the average knowledge before and after counseling using booklet media. Suggestions need to be made for further improvements to the booklet media, namely the size of the writing is enlarged. Further research is needed to see attitudes and behaviors so that they can be applied in integrated health posts.